COMPARARIVE STUDY OF EFFECT OF SUBSTITUENTS PRESENT ON CEPHALOSPORIN RING ON THE ANALYTICAL METHOD AND STATISTICAL PARAMETERS OF VARIOUS GENERATION DRUGS - Dilip M. Chafle (Journal of Global Pharma Technology, 2025)
Cephalosporin are very important class of antibiotic drugs which frequently prescribed by medical practitioners in modern allopathy for treatment of bacterial infections. In the present study Cefadroxil, Cefalexin, Cefaclor, Cefuroxime, Cefixime, Cefotaxime, Cefepime and Cefpirome drugs of various generation cephalosporin were selected. The spectrophotometric technique was used to study the effect of substituents of cephalosporin ring on the analytical method and statistical parameters of varios generation cephalosporin drugs. In the proposed method Fe (III) is reduced to Fe (II) by reacting with cephalosporin drug and then complexed with 1, 10 Phenanthroline. The reaction conditions for each drug such as maximum wavelength of absorption, time for complexation of reaction, volume of Fe (III) solution, volume of 1, 10 Phenanthroline solution and volume of phosphoric acid are optimized. The other parameters such as Beer’s law limit, molar absorptivity, Sandell’s sensitivity, regression equation and correlation coefficient have been determined. Lastly correlation of the substituent present on cephalosporin rings in various generations and their effect on analytical method and statistical parameters have been evaluated. Keywords: Spectrophotometry, Cephalosporin, Comparative study, Generation, Substituents.